Beyond Free Meals in Elementary Education: Rethinking School Nutrition Policy through Cultural Trust, Efficiency, and Islamic Justice in Indonesia - Taufikin Taufikin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
This study aims to analyze students' perceptions and satisfaction with the free nutritious meal program and to examine the efficiency of fund allocation from an economic and Islamic social justice perspective. Field research was conducted on 190 students from three elementary schools in Central Java using a mixed-method approach. Quantitative data were obtained through surveys, while qualitative data were collected through interviews with teachers, parents, cooks, and education observers. The results show that 91% of students prefer food cooked by their parents to food provided en masse by external parties. The main factors influencing student dissatisfaction include the poor taste of the food, concerns about food poisoning, and the fact that much of the food is not eaten at school but taken home or thrown away. From an efficiency perspective, providing cash assistance of IDR 15,000 directly to parents is considered more economical because it avoids operational costs and allows the National Nutrition Agency to continue monitoring nutrition. In addition, an analysis of social justice based on Islamic law shows that the program should focus on poor students (around 9% of the population), so that distribution is more equitable and the budget can be redirected to support primary school needs or improve teacher welfare. This study emphasizes that free nutritious food policies require a more adaptive approach that considers student satisfaction, budget efficiency, and social justice principles, so the goal of improving child nutrition can be optimally achieved.